Spojrzenie zwrócone ku wnętrzu - Melberg, Arne (Poznańskie Studia Polonistyczne. Seria Literacka, 2011)
This article presents an analysis of the transformations in the poetics of Rainer M. Rilke. According to the author, the essential impulse for the inception of this evolution had been provided by the encounter of the poet with a series of paintings by French artist Paul Cézanne. The author outlines particular traits in Rilkean poetic variants of modernism: the poet, drawing inspiration from the very same sources as many of his contemporaries (such as, for example, cubists), proposed his own conception of a poetic language. The most important element that constitutes a poem and a poetic image is the rhythm, the fundamental component in the organization of the text. Painterly “overlapping” of planes in a poem becomes thus a kind of a “breath” to take, that opens up a poem to the infinity underlined in the subject. From the experience gained in the visual arts concerning the “attitude and insight”, in turn, a poem attempts to organize a new arrangement for the presented space — ambiguous and in a constant movement.